Rewriting the Script (pp. 1--8) - Haerr, Megan (Ohio Journal of School Mathematics, 2019)
This paper outlines a lesson attempted in my classroom, the analysis of the outcomes of the lesson from my colleagues and the subsequent revisions made to the orignal lesson plan.